Statistical model to DNA melting - Augusto, Paulo Sergio Pilz; Drigo Filho, Elso; Ruggiero, Jose Roberto (Eclética Química, 2001)
We explore a DNA statistical model to obtain information about the behavior of the thermodynamics quantities. Special attention is given to the thermal denaturation of this macromolecule.